Cancer immunotherapy using γδT cells: dealing with diversity - Scheper, Wouter; Sebestyen, Zsolt; Kuball, Jürgen (Frontiers in Immunology, 2014)
The broad and potent tumour-reactivity of innate-like γδT cells makes them valuable additions to current cancer immunotherapeutic concepts based on adaptive immunity, such as monoclonal antibodies and αβT cells. Clinical success using γδT cells to treat cancer has so far fallen short however. Efforts of recent years have revealed a striking diversity in γδT cell functions and immunobiology, putting these cells forward as true “swiss army knives” of immunity. At the same time however, this heterogeneity poses new challenges to the design of γδT cell-based therapeutic concepts and could explain their rather limited clinical efficacy in cancer patients. This review outlines the recent new insights into the different levels of γδT cell diversity, including the myriad of γδT cell-mediated immune functions, the diversity of specificities and affinities within the γδT cell repertoire, and the multitude of complex molecular requirements for γδT cell activation. A careful consideration of the diversity of antibodies and αβT cells has delivered great progress to their clinical success; addressing also the extraordinary diversity in γδT cells will therefore hold the key to more effective immunotherapeutic strategies with γδT cells as additional and valuable tools to battle cancer.